Primer on engineering standards - Greulich, Owen R.; Jawad, Maan H. (John Wiley & Sons, Inc., 2018)
Standards supplement the design process by guiding the designer toward consistency, safety, and reliability. As daily life involves increasingly complex and sophisticated instruments, standards become indispensable engineering tools to ensure user safety and product quality. Primer on Engineering Standards: Expanded Textbook Edition delves into standards creation and compliance to provide students and engineers with a comprehensive reference.